PERAN KECERDASAN EMOSIONAL GURU PADA PENDIDIKAN ANAK USIA DINI - Farina, Mahlida; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Emotional intelligence is a crucial competence that influences teacher performance and the quality of the learning environment in early childhood education. This study aims to describe the role of teachers’ emotional intelligence in supporting classroom interactions, children’s engagement, and learning effectiveness at PAUD Suka Maju Kandangan. A descriptive qualitative approach was employed, involving three teachers with a minimum of two years of teaching experience. Data were collected through semi-structured interviews based on Goleman’s five dimensions of emotional intelligence and participatory classroom observations. Data analysis consisted of data reduction, data display, and conclusion drawing. The findings indicate that teachers’ emotional intelligence is reflected in their ability to manage emotions, demonstrate self-awareness, self-regulation, motivation, empathy, and social skills, which collectively contribute to a stable, supportive, and conducive classroom atmosphere for young children. Emotional intelligence enables teachers to respond constructively to instructional challenges and to meet children’s developmental needs, particularly in early childhood education settings with limited facilities. This study highlights the integrative nature of emotional intelligence and recommends continuous professional development programs focusing on teachers’ socio-emotional competencies to enhance the overall quality of early childhood education.